Microsoft lawsuits leave lawmakers divided over continued hearings. - Gruenwald, Juliana (CQ Weekly, 1998)
Many lawmakers contend that Congress has an important role to play in monitoring the issues raised by the Microsoft antitrust saga. They argue that Congress must continue examining questions about competition in the software industry raised by separate antitrust lawsuits filed on May 18, 1998, in the District Court in Washington, D.C., by the Justice Department and attorneys general from 20 states and the District of Columbia. These lawsuits allege that Microsoft Corp. attempted to leverage its monopoly in computer operating systems to achieve control over other software markets, such as Internet browsers. Microsoft's most vocal critic on Capitol Hill, Senate Judiciary Committee chairman Orrin G. Hatch, R-Utah, has stated that he intends to continue hearings on the issue. The Justice Department lawsuit has been criticized by some lawmakers, however, who blast the department for interfering in a competitive marketplace. The mixed reaction on Capitol Hill to continued congressional hearings and Microsoft's efforts to boost its image on the Hill are discussed.